STRATEGI PENINGKATAN KUALITAS PRODUK PERUSAHAAN BATIK: Studi Kasus Perusahaan Batik Nilo (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
Batik Nilo is a company engaged in the batik industry. The purpose of this research is to formulate the right strategy to be applied to the company. Data collection techniques used are observation, documentation, and interviews. Data analysis technique using IE matrix and SWOT matrix. The strategy obtained to determine the strategy to improve product quality, the results in Quadrant 1 are to support the aggressive Growth Oriented Strategy with the following strength and opportunity points: continue to increase the variety of motifs, maintain and improve the quality of natural coloring, and use quality raw materials.
Keywords: Strategy; Strenght; Weakness; Opportunities; Threats